Exercise-induced pulmonary hypertension: translating pathophysiological concepts into clinical practice - Naeije, Robert; Grünig, Ekkehard (Chest, 2018)
Exercise stress testing of the pulmonary circulation for the diagnosis of latent or early-stage pulmonary hypertension (PH) is gaining acceptance. There is emerging consensus to define exercise-induced PH by a mean pulmonary artery pressure > 30 mm Hg at a cardiac output < 10 L/min and a total pulmonary vascular resistance> 3 Wood units at maximum exercise, in the absence of PH at rest. Exercise-induced PH has been reported in association with a bone morphogenetic receptor-2 gene mutation, in systemic sclerosis, in left heart conditions, in chronic lung diseases, and in chronic pulmonary thromboembolism. Exercise-induced PH is a cause of decreased exercise capacity, may precede the development of manifest PH in a proportion of patients, and is associated with a decreased life expectancy. Exercise stress testing of the pulmonary circulation has to be dynamic and rely on measurements of the components of the pulmonary vascular equation during, not after exercise. Noninvasive imaging measurements may be sufficiently accurate in experienced hands, but suffer from lack of precision, so that invasive measurements are required for individual decision-making. Exercise-induced PH is caused either by pulmonary vasoconstriction, pulmonary vascular remodeling, or by increased upstream transmission of pulmonary venous pressure. This differential diagnosis is clinical. Left heart disease as a cause of exercise-induced PH can be further ascertained by a pulmonary artery wedge pressure above or below 20 mm Hg at a cardiac output < 10 L/min or a pulmonary artery wedge pressure-flow relationship above or below 2 mm Hg/L/min during exercise.